OBTAINING NATURAL MEDICINES FROM PLANTS (Scientific journal of the Fergana State University, 2024)
Medicinal plants have been used for centuries to treat various ailments and promote well-being. This article covers the process of extracting medicinal plants, a systematic approach that maximizes their therapeutic benefits.